Republic of Chad : Priorities for Ending Poverty and Boosting Shared Prosperity - World Bank Group (World Bank, Washington, DC, 2015)
This systematic country diagnosis (SCD) for Chad aims to identify how to achieve the twin goals of ending poverty and improving shared prosperity. It acknowledges both: (i) the need for selectivity in pro-poor interventions, and (ii) the inherent difficulty to do so given the many competing binding reasons for poverty. Selectivity means the identification of principal opportunities for sustainable poverty reduction in the next 15 years, as well as the identification of binding constraints to reaping such opportunities. Selectivity also implies making trade-offs between immediate and longer term objectives, with priority given to the identification of poverty reduction opportunities which will: (i) deliver the highest possible results before 2030, and (ii) not undermine prospects for poverty reduction and shared prosperity beyond 2030. The analysis presented in the SCD draws on a variety of information sources. These include domestic statistics and reports, evaluations by the country’s development partners, original research conducted by the World Bank team, and consultations held in N’Djamena with nongovernmental organizations and the private sector. Reaping poverty reduction opportunities will require addressing a selected number of binding constraints.